Mechanical Responses to Different Excavation Methods of Qichongcun Tunnel in Guiyang City, China. (13th August 2021) - Xie, Siwei; Huang, Feng; Wang, Guihe; Zhu, Chaoyang; Su, Yunji; Qian, Feng
Abstract : The construction method of tunnel has a critical impact on the stress and strain field during excavation. This study simulated the construction of Qichongcun tunnel by applying a different excavation method, including double-sided method, single-sided method, and three-step dynamic balance excavation method. The distribution and variation of the stress, vertical displacement, horizontal displacement of surrounding rocks, and stress of initial and secondary lining were studied. The results showed that large displacement of surrounding rocks would be induced during the construction in three-step method, but the stress of the second lining was small after completion of the construction. The displacement and stress of the three-step dynamic balance excavation method were larger than those of the other two methods, but it still met the requirements of safety.